PENGARUH KOMPENSASI DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN - Yakup . (Journal of Management Small and Medium Enterprises (SMEs), 2016)
The purpose of the research to analyze the influence of compensation and promotion towardemployee job satisfaction. Data was collected using a census to 37 employee of the Islamic PawnshopBranch of Gorontalo. Data were analyzed using multiple linier regression, the results showed apositive and significant influence of compensation and promotion toward employee job satisfaction.Keywords: Compensation, Promotion, Job Satisfaction